FAKTOR PERNIKAHAN DI BAWAH TANGAN, MASYARAKAT YANG BERAGAMA ISLAM DI DESA BUKMAKONG, KECAMATAN SINGKAWANG SELATAN - Rovika, Devi; Hasan, Muhammad; Hakimah, Nur (Al-Usroh, 2024)
The purpose of this article is to find out the causes of underage marriage in Bukmakong Village, South Singkawang District. In this research uses empiricalsociological methodology with qualitative methodology. Researchers used primary data sources, such as interviews with nine perpetrators of underages marriages, as well as secondary data sources such as books, journals, laws and regulations, as well as religious leaders or headmen who married people secretly or unrecorded. Acceptance researchers conducted structured interviews to obtain data, and carried out member checks were conducted to verify the truth of the data. The data analysis process uses data reduction techniques, data visualization and drawing conclusions. The results showed several factors, such as out of wedlock pregnancy, economic factors, geographical distance, obedience of students to their kiai in order to get the for the blessing of community in the process of taking care of administrative files at the Religious Affair Office (KUA).